The advance of research governance in psychiatry: one step forward, two steps back. (29th May 2013) - Leeson, V. C.; Tyrer, P.
Abstract : Purpose: To investigate the reasons behind difficulties in recruiting patients to randomized controlled trials (RCTs) in psychiatry and to examine a database of RCTs for differences between studies in mental health and other specialities. Methods: A discussion of recent changes in research governance in the UK and Europe followed by an examination of the database of all trials supported by the Health Technology Assessment programme of the National Institute of Health Research in the UK between 1993 and 2007 to determine if three different measures, (i) time between grant approval and study start date, (ii) percentage of additional time given to extend recruitment and (iii) percentage of planned recruitment achieved, changed over the time period studied and differed between mental health, cancer and other medical disciplines. Findings: Despite attempts in the UK to accelerate the process of clinical trials in recent years, there was a significant increase in the extension time for trials to be completed ( p  = 0.038) and the percentage of planned recruitment to mental health studies (71%) was significantly less than for cancer (90.3%) and other studies (86.1%) ( p  = 0.032). Summary: These results suggest that, despite the priority afforded to the advancement of RCTs in healthcare, such studies are encountering increasing difficulty in recruiting to time and target. We suggest that this difficulty can be attributed, at least in part, to the excessively byzantine regulation and governance processes for health research in the UK, and unnecessary bureaucracy in the current National Health Service system. Mental health studies appear particularly vulnerable to delay and better systems to facilitate recruitment are required urgently for the evidence base to be improved and facilitate new cost-effective interventions.